The market research toolbox : a concise guide for beginners - McQuarrie, Edward F. (Thousand Oaks, Calif. : SAGE Publications, 2012)
'An ideal resource for those who want to conduct market research but have little experience in doing so, The Market Research Toolbox describes how to think of market research in the context of making a business decision. The book begins by defining market research and discussing some of the various types and techniques. It then examines what objectives can be met by doing market research and the expected payoffs. This text explores market research techniques such as secondary research, customer visits, focus groups, surveys, choice modeling and experimentation. The author describes how each technique works along with its costs and uses, tips for success, when and how to use certain techniques and precautions to take while using them. The Third Edition of The Market Research Toolbox incorporates new material on Web surveys along with more information on data analysis and sampling theory for qualitative research. Additionally, a new closing chapter illuminates the limitations of market research to clarify when it should be employed. What's New sections have been added to every chapter and new examples are included throughout the text, along with updated suggested readings and references'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Marketing research -- Methodology